IDENTIFIKASI KELAYAKAN FASILITAS RUANG BERMAIN RAMAH ANAK DI WISATA PANTAI BIRU - Fitriannisa Ramadhani; Fajar Luqman Tri Ariyanto; Dinda Rizki Tiara (Universitas Islam Lamongan, 2022)
The government is committed to achieving the Subtainable Development Goal or SDG's targets, especially those related to child development at the Regency/City level. Protection of children in order to fulfill children's rights to grow and develop without discrimination, one of which is building child-friendly spaces as explained in Law No. 23 of 2001 Article 56 (1) concerning efforts to obtain children's play facilities by fulfilling health and safety requirements. Limited public facilities force people to be creative in managing the natural environment, one of which is in the beach tourism sector by paying attention to child-friendly play rooms. This study aims to analyze the implementation of child-friendly tourism programs at Blue Beach Tourism, Bangkalan Regency. The selection of the Blue Beach Tourism location is because it provides children's playgrounds and is dominated by children visitors. The study used a qualitative case study method with interview, documentation, and observation techniques. Based on the analysis results show that there is no exploitation and discrimination in the blue beach and blue beach tourism areas have adequate facilities by caring for and maintaining these tourist facilities.